Enhancing innovation culture: The case of multinational advertising agency VMLY&R Lisboa - Rocha, R. T.; Ferreira, F.; Milici, A.; Banaitienė, N.; Banaitis, A. (Technological and Economic Development of Economy, 2022)
The world is going through an unprecedent experience marked by one of the most serious pandemic to date. Companies currently face multiple challenges, including maintaining their organizational culture while defining and validating new working and business models and completely rethinking past competitive advantages. Innovation is a fundamental part of these processes. This study identifies the main findings in the literature on company culture and the promotion of innovation within organizations. Problem structuring methods (i.e., design thinking (DT) and decision making trial and evaluation laboratory (DEMATEL)) were applied to explore innovation culture further and apply the results to the multinational advertising agency VMLY&R Lisboa in order to delineate this company’s culture and enhance its potential for innovation. An expert panel was recruited to develop a fuller understanding of the cause-effect relationships between factors that influence innovation and to enable a more collaborative, constructivist approach to this decision problem. The main findings were validated by VMLY&R Lisboa’s chief executive officer, and concrete initiatives were proposed that can enhance this company’s innovation culture. The study’s contributions and limitations are also discussed.